Keanekaragaman dan Penetapan “Umbrella Species” Satwa liar Di Taman Nasional Gunung Leuser - Wanda Kuswanda; Sriyanti Puspita Barus (Foresty Faculty of Hasanuddin University, 2017)
The determination of ‘umbrella species’ in the wildlife conservation implementation is very important to be effective and directed. This study was aimed to obtain information wildlife diversity (primates and terrestrial mammals) and ‘umbrella species’ on various type of habitats to support conservation programs in the Gunung Leuser National Park (GLNP), of Besitang Watershed, North Sumatera. The research was carried for six months, from May to October 2015. The observation was made using combination of variable circular plot and strip transect methods. Determination of 'umbrella species' is done through valuating by referring to the Department of Forestry criterias (2008). Primate were identified about 6 species and terrestrial mammal of 16 species. Primate and mammal diversity index are with the category of low to moderate with abudance index between 5.60-15.32. Based onassessment criteria and consideration to high conflict potential show that ‘umbrella species’ are elephant (Elephas maximus sumatranus Temminck, 1847). The wildlife conservation implications are recommended, such as to the elephants around GLNP, i.e to increase research wildlife distribution and population, habitat protection and population pockets, to develop a database and monitoring with geographic information systems (GIS), the minimization a hunting and law enforcement as well as mitigation wildlife conflicts, such as elephants and orangutans.